Erythrocyte tropism of malarial parasites: The reticulocyte appeal - Leong, Yew Wai; Russell, Bruce; Malleret, Benoit; Rénia, Laurent (Frontiers in Microbiology, 2022)
Erythrocytes are formed from the enucleation of erythroblasts in the bone marrow, and as erythrocytes develop from immature reticulocytes into mature normocytes, they undergo extensive cellular changes through their passage in the blood. During the blood stage of the malarial parasite life cycle, the parasite sense and invade susceptible erythrocytes. However, different parasite species display varying erythrocyte tropisms (i.e., preference for either reticulocytes or normocytes). In this review, we explore the erythrocyte tropism of malarial parasites, especially their predilection to invade reticulocytes, as shown from recent studies. We also discuss possible mechanisms mediating erythrocyte tropism and the implications of specific tropisms to disease pathophysiology. Understanding these allows better insight into the role of reticulocytes in malaria and provides opportunities for targeted interventions.